Anwendung der Vorhersage von Schiff-Eis-Interaktion : Abschlussbericht PrICE ... : PrICE ... - Lübcke, Adele; Hahn, Malte; Johnsen, Lars; Leemkuil, Klaas-Jan (Pella Sietas Werft, 2020)
Illustrationen, Diagramme ...